Modelling the biogeochemical footprint of rivers in the Hauraki Gulf, New Zealand - Macdonald, Helen; Collins, Charine; Plew, David; Zeldis, John; Broekhuizen, Niall (Frontiers in Marine Science, 2023)
Building accurate physical-biogeochemical models of processes driving climate and eutrophication-related stressors in coastal waters is an essential step in managing the impacts of these stressors. Here we develop a coupled physical-biogeochemical model to investigate present day processes for a key marine ecosystem in Aotearoa, New Zealand: The Hauraki Gulf/Firth of Thames system. Simulation results compared well with an accompanying long-term (decadal) observational dataset, indicating that the model captured most of the physical and biological dynamics of the Hauraki Gulf/Firth of Thames system. This model was used to investigate the riverine and cross shelf exchanges of nutrients in the region and showed that only a small number of large rivers within the Firth of Thames dominated the freshwater inputs, with phytoplankton concentrations driven by nutrient inputs from these rivers. However, while riverine inputs dominated the biological response in the Firth of Thames, cross-shelf fluxes dominated the biological response in the outer Hauraki Gulf region. Nutrients from both sources were balanced by a sediment denitrification flux. Analyses were conducted to examine agreement of observations with subsampled and climatological model outputs. These revealed that modelling effort needs to focus on the representation of sediment fluxes and parameterizations during the autumn, and the observational effort needs to focus on increased temporal data collection during summer to better understand biases in seasonal climatologies derived from model and observations. These results are valuable for demonstrating effects of land-derived and oceanic drivers of the biogeochemical dynamics of the Hauraki Gulf/Firth of Thames system.